2022
DOI: 10.1039/d2py00195k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and molecular characterization of well-defined polyanion miktoarm star copolymers

Abstract: Over the last year, the synthesis of polyanion copolymers has attracted considerable attention for their utilization in single-ion electrolytes in lithium battery applications. Morphology has a significant impact on the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
(45 reference statements)
0
7
0
Order By: Relevance
“… a The sample abbreviation, i.e., (PSTFSILi) 22 (PEO) 22 ( x _105), corresponds to the molar ratio between EO (105) and STFSILi ( x ) monomeric units. The average number of EO units per PEO arm is 105, so we chose to use this as a reference. b Calculated from 1 H NMR. c Taken from DSC measurements reported in a previous publication …”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“… a The sample abbreviation, i.e., (PSTFSILi) 22 (PEO) 22 ( x _105), corresponds to the molar ratio between EO (105) and STFSILi ( x ) monomeric units. The average number of EO units per PEO arm is 105, so we chose to use this as a reference. b Calculated from 1 H NMR. c Taken from DSC measurements reported in a previous publication …”
Section: Resultsmentioning
confidence: 95%
“…It is well accepted and reported that in PEO-based electrolytes the ion conductivity is strongly affected by the crystallization behavior of PEO and its glass-transition temperature. So we start our discussion by revisiting the effect of star-shaped macromolecular architecture and the degree of polymerization of the PSTFSILi arms on the thermal properties of the single-ion polyelectrolytes, as we recently reported . The miktoarms (PSTFSILi) 22 (PEO) 22 with r > 0.046 remained amorphous as the crystallization behavior of PEO was fully suppressed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other configurations also include block copolymers, 100 graft polymers, 101 star polymers, 102 etc. For example, block copolymers usually include soft segments and hard segments, in which the hard segments are used to increase the mechanical modulus, while the soft segment is used for lithium ion transmission.…”
Section: Mechanism Of Lithium-ion Transport In Solid Polymer Electrol...mentioning
confidence: 99%
“…Nitrogen−oxygen radicals cannot initiate monomer polymerization or other reactions, and Tempo nitroxides are generally required as radical scavenger to form covalent bond dormant species, which are poorly versatile and are mainly used in the synthesis of polystyrene-based polymers. 49,50 In ITP, the concentration of the propagating radical is regulated by a reversible chain transfer reaction between the propagating radical and the iodine transfer agent. 52−54 Later, reversible iodine transfer polymerization (RITP) is developed, in which molecular iodine directly participates in the radical polymerization and the chain transfer agent is in situ formed during the reaction.…”
Section: Introductionmentioning
confidence: 99%